Evolution of the dorsal-ventral patterning network in the mosquito, Anopheles gambiae - Goltsev, Y; Fuse, N; Frasch, Manfred; Zinzen, RP; Lanzaro, G; Levine, Michael (Development, 2007)
The dorsal-ventral patterning of the Drosophila embryo is controlled by a well-defined gene regulation network. We wish to understand how changes in this network produce evolutionary diversity in insect gastrulation. The present study focuses on the dorsal ectoderm in two highly divergent dipterans, the fruitfly Drosophila melanogaster and the mosquito Anopheles gambiae. In D. melanogaster, the dorsal midline of the dorsal ectoderm forms a single extra-embryonic membrane, the amnioserosa. In A. gambiae, an expanded domain forms two distinct extra-embryonic tissues, the amnion and serosa. The analysis of approximately 20 different dorsal-ventral patterning genes suggests that the initial specification of the mesoderm and ventral neurogenic ectoderm is highly conserved in flies and mosquitoes. By contrast, there are numerous differences in the expression profiles of genes active in the dorsal ectoderm. Most notably, the subdivision of the extra-embryonic domain into separate amnion and serosa lineages in A. gambiae correlates with novel patterns of gene expression for several segmentation repressors. Moreover, the expanded amnion and serosa anlage correlates with a broader domain of Dpp signaling as compared with the D. melanogaster embryo. Evidence is presented that this expanded signaling is due to altered expression of the sog gene.
Keywords: mosquito; anopheles gambiae; embryo; gastrulation; amnion; serosa; gene network; Sog; Dpp; Zen; dorsal-ventral patterning